Legal Nature of Concessionaire and Public-private Partnership Contracts (Journal of Legal Studies, 2023)
This paper aims to analyze the legal nature of concessionaire and PPP contract in Albanian Legislation and through the perspective of European legislation analyzing mainly the Italian and French legislation and doctrine in this area. The main hypothesis that this paper aims to address is related to the fact, if it is enough to categorize these kinds of contracts with a hybrid status between public and private law, or the fact that so many countries appellate more and more to the concessionaire and PPP contracts is the momentum to create a separate law discipline as so many universities in France, USA, Japan do.  Also, this paper aims to make a comparative study of Albanian legislation in the area of concessionaire and PPP contracts with the European legislation being the fact that for Albania this is a new area, and is a considerable lake of doctrine and legal studies that analyze the specifics and characteristics of such kind of contracts, putting at the last instance not only the Albanian contractual authorities but also the national courts in difficulties of implementation and interpretation.